The role of internal and international relative deprivation in global migration - Czaika, M; de Haas, H (International Migration Institute, 2011)
This paper analyses the role of internal (within-country) and international (bilateral and global) relative deprivation and absolute deprivation in international migration. It is argued that these three forms of relative deprivation need to be simultaneously taken into account in order to advance our theoretical understanding of the complex drivers of migration processes. Empirical analysis based on 2000 global migrant stock data suggests that absolute deprivation constrains emigration while international relative deprivation and internal relative deprivation in destination countries fuel migration. The effect of internal relative deprivation in origin countries is small and rather ambiguous. The results highlight complex and often counter-intuitive ways in which relative and absolute deprivation affect migration. The paper suggests that it would be unfounded to expect that decreases in international and internal relative and absolute deprivation will lead to massive reductions in the volume of international migration.